Tuberculosis among people living with HIV/AIDS in Jazan Region, Southwestern Saudi Arabia. Issue 11 (November 2021) - Darraj, Majid A.; Abdulhaq, Ahmed A.; Yassin, Abuobaida; Mubarki, Sultan; Shalaby, Heba M.; Keynan, Yoav; Ghailan, Khalid Y.; Al-Mekhlafi, Hesham M.
Abstract: Background: Tuberculosis (TB) and human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) infections are leading causes of morbidity and mortality worldwide. People living with HIV/AIDS (PLWHA) are highly susceptible to TB infection and progression to active TB disease. This study aims to determine the proportion and risk factors of TB among PLWHA in Jazan Region, southwestern Saudi Arabia. Methods: A cross-sectional study was conducted among HIV-infected individuals attending the main referral hospital in Jazan Region during the period 2017–2019. The participants' TB status, CD4+ lymphocyte count, and viral load were assessed. In addition, their demographic and clinical information was collected using a structured questionnaire. Results: A total of 316 HIV-positive individuals aged between 13 and 81 years (75% male and 25% female) were enrolled in this study. Of them, 30 (9.5%; 95% confidence interval [CI]: 5.2, 10.6%) were diagnosed with TB: 46.7% (14/30) had pulmonary TB and 53.3% (16/30) had extrapulmonary TB. The highest proportion of TB-positive PLWHA was found among participants aged 18–30 years (11.6%) and among non-Saudis (14.0%) when compared to other age groups and Saudi participants (7.4%). Multivariate analysis showed that male gender (adjusted odds ratio [AOR] = 4.79; 95% CI = 1.22, 18.74), past medical history (PMH) of TB (AOR = 29.67; 95% CI = 5.31, 164.32), PMH of other RTIs (AOR = 5.86; 95 % CI = 2.14, 16.06), CD4+ lymphocyte count of <200 cells/mm³ (AOR = 4.33; 95% CI = 1.65, 11.36), and viral load of ≥1 × 10 3 copies/mL (AOR = 5.46; 95% CI = 2.02, 14.77) were the significant risk factors of TB among the studied PLWHA. Conclusion: The prevalence of TB/HIV co-infection among the studied population was 9.5%. Therefore, all PLWHA should be screened for TB at every visit to a health facility. The findings highlight that integration of health services for both TB and HIV/AIDS in Saudi Arabia is recommended.